EVALUATION OF RISK OF TRANSFUSION-TRANSMISSIBLE INFECTIONS IN BLOOD DONORS AT THE LAQUINTINIE HOSPITAL IN DOUALA, CAMEROON - Medi, Christiane Sike; Ayangma, Celestin Roger; Voundi, Esther; Ndoumba, Annick Mintya; Ngogang, Marie Paule; Eyoum, Bertrand Bille; Embolo, Elisée Enyegue; Essomba, Noël Emmanuel (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Unsafe blood transfusions have the potential to transmit a variety of infections known as transfusion-transmitted infections (TTIs). The overall objective of our study was to determine the seroprevalence and factors associated with TTIs related to human immunodeficiency virus (HIV), hepatitis B virus (HBV), hepatitis C virus (HCV), and Treponema pallidum bacteria among blood donors at the Laquintinie Hospital in Douala. Methodology: A cross-sectional analytical study was conducted among blood donors at the HDH for 12 months, from January 1 to December 30, 2021. HIV, HBV and HCV serological markers were tested by two immunological techniques, immuno-chromatography and Enzyme-Linked Immunosorbent Assays (ELISA). Treponema pallidum infection was tested by hemaglutination and ELISA. Factors associated with infection were investigated by multinomial logistic regression with a statistical significance level of 5%. Results: We analyzed 7222 blood bags, 1010 of which were positive for at least one of the infectious markers, i.e. a prevalence of TTI of 14.0%; this prevalence was significantly higher in male donors (p=0.001), those aged between 45 and 54 years (p=0.009), workers in the private sector (p=0.003), married donors (p=0.034). No significant difference was observed between compensatory and voluntary donation. Conclusion: TTIs remain a major public health concern, hence the need for awareness and surveillance strategies.